Сytomegalovirus infection as a pathology predictor in fetuses, newborns and children of early age - О. О. Kulia (Zaporožskij Medicinskij Žurnal)
Aim. The relevance of cytomegaloviral infection is caused by perinatal loss and disorders of varying severity. The specialized literature has been reviewed in order to compile and present a modern view on the etiology, possible pathogenetic mechanisms, to describe the main clinical symptoms, the current strategy of diagnosis, treatment and prevention of cytomegalovirus infection of infants.